Unsur Intrinsik Roman “Das Doppelte Lottchen” Karya Erich Kästner - Muh. Haeqal; Hasmawati Hasmawati (Universitas Negeri Makassar, 2022)
Abstract. This research aims to describe the intrinsic elements in the form of theme, plot, setting, character, point of view, messagge and the value of character education in the novel “das Doppelte lootcchen” by Erich Kästner. Teh data of this research are primary data and secondary data. Primary data is direct data from the novel text “das Doppelte Lottchen”. Secondary data is supporting data that contains additional information in the form of books, journals, and articles. Data were analyzed based on qualitative approach with content analysis. The results of the research are as follows, a description of the theme element: family, plot elements: combined plot, background elements, place settings: at hte children’s House, holiday time setting, and social beliefs background, character elements: main and additional characters, corner elements point of view: using a third person point of view, mandate: true happines. The interrelationships between the intrinsic elements of fairy tales include the theme, plot, setting, character, point of view, and message. Character education values include religious values, integrity values, mutual cooperation values, and independent values.Keywords: Intrinsic Element, Content Analysis, Das Doppelte Lottchen, Erich Kästner